Assessing the role of international financial institutions in supporting the Iraqi economy (Eurasian Journal of History, Geography and Economics, 2022)
The economic conditions and challenges that Iraq is going through have forced it to resort to international financial institutions in order to obtain the necessary funding to support the country’s economic progress and achieve sustainable development goals, but this did not contribute to activating the economic reform movement, and the actual application of that policy was weak despite the availability of liquidity and the international monetary reserve for reasons that are well-known and represented by insecurity, political and economic instability, and economic rent